Thei Analysis of Odd-Even Policies in Reducing Pollution Problems in Jakarta - Sari, Ade Risna; Nugroho, Budi Sulistiyo; Sasongko, Restu Widyo; Nugraha, Agus Bambang; Munizu, Musran (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Pollution pollution in Jakarta is one of the hot topics of discussion among the community. The main factor causing air pollution in Jakarta is the increasing number of emissions due to the increasing number of transportation vehicles. One solution to this problem is the Odd-Even Policy. Therefore, this research aims to analyze the Odd-Even Policy in overcoming pollution problems in Jakarta. This research is quantitative research with an explantory approach, namely research that uses previous research as a stepping stone to find new variations including novelty and research gaps. The research results show that the Odd-Even Policy is effectively implemented in order to reduce pollution problems in Indonesia.